Pengenalan Pemrograman Python bagi Siswa SMP Negeri 04 Kota Bengkulu sebagai Upaya Meningkatkan Literasi Digital - Ramadhani, Indhyra; Saputra, M. Arya; Salsabilla, Rachma Naura; Hakim, Wahyu Rahman; Al'Hadid, Yuda; Fitriah, Fitriah (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
The rapid development of the digital era requires young generations to possess strong technological literacy from an early age. However, junior high school students often lack a basic understanding of programming and computational logic. At SMP Negeri 4 Kota Bengkulu, ICT learning still focuses on theoretical aspects and office tools rather than coding. Therefore, this community service activity was carried out to introduce basic Python programming as an effort to improve students’ digital literacy. The objective of this program was to equip students with foundational knowledge of programming, spark interest in technology, and support future curriculum development in coding-based ICT. The method used was a one-group pretest-posttest design, complemented by observation and questionnaires. The training involved 24 students from grades VII to IX. The evaluation showed significant improvement in student understanding, with an average score increase exceeding 150%. Student enthusiasm was high, the learn-by-doing approach proved effective, and Python’s simplicity made it suitable for beginners. This program concludes that Python programming introduction is a strategic step to strengthen digital literacy among junior high school students.